Improved high-toughness M2 high-speed steel flux-cored wire and preparation method thereof
By using the technology of improved high-toughness M2 high-speed steel flux cored welding wire in M2 high-speed steel welded powder, the problems of high production costs and insufficient toughness of existing M2 high-speed steel welded powder are solved, high toughness and wear resistance are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411956065.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-18
AI Technical Summary
The production cost of existing M2 high-speed steel deposit powder is high and the product is not tough enough, and the heat treatment process is complex, resulting in further increase in production costs.
Improved high-toughness M2 high-speed steel flux-core welding wire is used, and its chemical compositions include boron, carbon, silicon, manganese, vanadium, nickel, cobalt, chromium, niobium, molybdenum, tungsten and other elements. Through specific element combinations and process treatment, the toughness and wear resistance of the welding wire are improved.
It achieves high toughness and wear resistance, reduces production costs, and is simple in process, which is suitable for industrial production.
Smart Images

Figure CN119635071A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material processing welding materials, and in particular relates to an improved high-toughness M2 high-speed steel flux-cored welding wire and a preparation method thereof. Background Art
[0002] High-speed steel is a tool steel with high hardness, high wear resistance and high heat resistance. It is widely used in the manufacture of cutting tools for cutting difficult materials, such as saw blades, cutting tools, cutter heads, drill bits, milling cutters, etc. It is also suitable for molds that withstand vibration and impact loads, such as hot forging molds, hot extrusion molds, hot working molds, die-casting molds, etc.
[0003] At present, in order to form a coating with the same performance as high-speed steel through welding, the market mostly adopts plasma cladding powder or laser cladding powder. Among them, the representative of plasma cladding powder is M2 high-speed steel cladding powder, and the representative of laser cladding powder is M2 powder metallurgy high-speed steel. However, the cladding powder method has the following defects: ① High production cost. The production cost of plasma cladding powder or laser cladding powder is 170-180 yuan / kg, which is a large cost expenditure for enterprises. ② The product toughness of the cladding powder is insufficient. In the production process, heat treatment is required, the process is complicated, and the relative production cost is increased.
[0004] Based on the above reasons, the present application provides an improved high-toughness M2 high-speed steel flux-cored welding wire and a preparation method thereof by optimizing M2 high-speed steel. Summary of the invention
[0005] One object of the present invention is to provide an improved high-toughness M2 high-speed steel flux-cored welding wire, and another object of the present invention is to provide a method for preparing the improved high-toughness M2 high-speed steel flux-cored welding wire.
[0006] To achieve the first object of the present invention, the following technical solution is adopted:
[0007] An improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprises an outer skin and a flux core filled in the outer skin, and the chemical composition of the deposited metal of the flux-cored welding wire comprises the following components by weight percentage:
[0008] Boron B: 0.5~1.6%; Carbon C: 0.6~1.3%; Silicon Si: 1~1.6%; Manganese Mn: 0.3~0.9%; Vanadium V: 1~2.2%; Nickel Ni: 0.3~0.7%; Cobalt Co: 0.3~0.7%; Chromium Cr: 3~8%; Niobium Nb: 1.5~2.2%; Molybdenum Mo: 5%; Tungsten W: 6%; The balance is iron.
[0009] The present invention will be further described below:
[0010] In the present invention, each component element of the flux-cored welding wire has a corresponding function, as follows:
[0011] The role of the boron (B) element is to strengthen the matrix and refine the grains, thereby improving the strength, hardness, plasticity and toughness of the flux-cored welding wire.
[0012] The role of the carbon (C) element is to strengthen the matrix and generate a hard phase, thereby making the flux-cored wire have a phase with high hardness and high melting point.
[0013] The role of silicon (Si) is to strengthen the matrix and stitch the grain boundaries, making the grain boundaries between the grains in the flux-cored welding wire more regular and tight, thereby improving the strength, plasticity and toughness of the flux-cored welding wire.
[0014] The role of manganese (Mn) element is to strengthen and toughen the matrix, thereby improving the strength and toughness of the flux-cored wire, absorbing the energy generated by the flux-cored wire during surfacing, and reducing the generation and expansion of cracks.
[0015] The role of vanadium (V) element is to refine the grains and generate dispersed high-hardness non-sharp-angle reinforcement phase, thereby enhancing the strength and hardness of the flux-cored welding wire. Due to the absence of sharp angles, the reinforcement phase can distribute the stress more evenly and avoid the phenomenon of stress concentration, thereby reducing local damage and crack initiation of the flux-cored welding wire. The reinforcement phase can also form a barrier inside the material to hinder the expansion of existing cracks, thereby improving the fracture toughness of the flux-cored welding wire; furthermore, the reinforcement phase also has good thermal stability and wear resistance, which makes the flux-cored welding wire have high wear resistance and temperature resistance.
[0016] The role of nickel (Ni) element is to strengthen and toughen the matrix and neutralize the hard phase performance, thereby improving the strength and toughness of the flux-cored wire. It can also inhibit the propagation of cracks and help improve the overall stability and durability of the flux-cored wire.
[0017] The role of cobalt (Co) element is to strengthen and toughen the matrix and neutralize the hard phase performance. The role of Co element is consistent with that of Ni element, both of which are to improve the overall stability and durability of flux-cored welding wire.
[0018] The role of chromium (Cr) element is to neutralize and optimize the affinity between the matrix and the reinforcement, reduce the crack tendency, and thus reduce the occurrence of cracks in the flux-cored welding wire.
[0019] The role of niobium (Nb) element is to refine the grains, toughen the matrix, and generate dispersed high-hardness non-sharp-angle reinforcement phase. The role of Nb element is similar to that of V element, but the difference is that it can also enhance the toughness of flux-cored welding wire.
[0020] The role of molybdenum (Mo) element is to neutralize and optimize the matrix and reinforce the affinity, reduce the crack tendency, and improve the corrosion and temperature resistance, thereby improving the strength, high temperature resistance and corrosion resistance of the flux-cored welding wire, while inhibiting the initiation of cracks.
[0021] The role of tungsten (W) element is to strengthen the matrix and improve the temperature resistance, thereby enhancing the strength and high temperature resistance of the flux-cored welding wire.
[0022] Preferably, the chemical composition of the deposited metal of the flux-cored welding wire comprises the following components by weight percentage:
[0023] Boron B: 1.0%; Carbon C: 0.9%; Silicon Si: 1.3%; Manganese Mn: 0.6%; Vanadium V: 1.6%; Nickel Ni: 0.5%; Cobalt Co: 0.5%; Chromium Cr: 6%; Niobium Nb: 1.9%; Molybdenum Mo: 5%; Tungsten W: 6%; Iron: 74.7%.
[0024] Preferably, the chemical composition of the deposited metal of the flux-cored welding wire also includes aluminum, and the weight percentage of the aluminum is 0.2-0.5%. The aluminum exists in the form of aluminum powder, wherein the aluminum (Al) element can improve the toughness of the surfacing deposited metal of the flux-cored welding wire, will not produce a cutting effect on the matrix of the deposited metal, and improves the toughness of the flux-cored welding wire. High-quality aluminum powder has the characteristics of high purity and few impurities, so aluminum powder is used as the source of the aluminum element in the flux-cored welding wire.
[0025] Preferred:
[0026] The boron exists in the form of boron carbide and borax. Boron carbide has high wear resistance, high hardness and good chemical stability. Adding boron carbide can improve the hardness and wear resistance of flux-cored welding wire. Borax can purify the metal surface, promote flux flow, improve welding efficiency and improve the quality of welds.
[0027] The carbon exists in the form of graphite, which has high temperature resistance and can improve the high temperature resistance of the flux-cored welding wire. Therefore, it can be used as a source of carbon element in the flux-cored welding wire.
[0028] The silicon exists in the form of 75% ferrosilicon, and silicon atoms combine with iron atoms to form silicon-containing ferrite with strong covalent bonds, which not only promotes the formation of ferrite, but also significantly strengthens the ferrite. The combination of the two improves the strength, plasticity and toughness of the flux-cored welding wire. Therefore, ferrosilicon is used as the source of silicon in the flux-cored welding wire.
[0029] The manganese exists in the form of electrolytic manganese, which has high strength and hardness, and also has certain plasticity and toughness, and can improve the strength, hardness and toughness of the flux-cored welding wire, and can provide more manganese elements for the flux-cored welding wire;
[0030] The vanadium exists in the form of 80% ferrovanadium, which has good corrosion resistance, can remain stable in harsh chemical environments, and can improve the corrosion resistance of flux-cored welding wire;
[0031] The chromium exists in the form of 68% high carbon ferrochrome, which has the characteristics of good chemical stability, wear resistance and high hardness, and can improve the wear resistance and hardness of the flux-cored welding wire. Therefore, it is used as the source of chromium in the flux-cored welding wire;
[0032] The niobium exists in the form of 60% ferroniobium, which has a high melting point, good ductility and corrosion resistance, so niobium powder is used as the source of niobium element in the flux-cored welding wire;
[0033] The molybdenum exists in the form of 60% molybdenum iron. The 60% molybdenum iron alloy has a uniform fine-grained structure, which can improve the hardenability of the molybdenum iron alloy and help eliminate temper brittleness, thereby improving the strength and wear resistance of the flux-cored welding wire. Therefore, it can be used as a source of molybdenum in the flux-cored welding wire;
[0034] The tungsten, the nickel and the cobalt exist in the form of 80% tungsten carbide cemented carbide. The 80% tungsten carbide cemented carbide contains tungsten, nickel and cobalt elements. The 80% tungsten carbide cemented carbide has high hardness and good wear resistance. Therefore, it is used as the source of tungsten, nickel and cobalt elements in the flux-cored welding wire.
[0035] The iron exists in the form of iron powder, which can be added to the deposition rate in the flux-cored welding wire and combined with other metals to form a weld with certain strength and toughness.
[0036] Preferably, the flux core in the flux-cored welding wire comprises the following components in parts by weight:
[0037] Boron carbide 1.9-6.1 parts; borax: 1.5-1.8 parts; graphite 0.4-0.9 parts; 75% ferrosilicon 3.8-6.2 parts; electrolytic manganese 0.4-1.1 parts; 80% ferrovanadium 4.3-9.4 parts; 68% high carbon ferrochrome 12.2-32.5 parts; 60% ferroniobium 6.4-9.4 parts; 60% ferromolybdenum 22.7 parts; 80% tungsten carbide 23.1 parts; iron powder 2.7-3.1 parts.
[0038] More preferably, the flux core in the flux cored welding wire comprises the following components in parts by weight:
[0039] 3.8 parts of boron carbide; 1.7 parts of borax; 0.7 parts of graphite; 5.0 parts of 75% ferrosilicon; 0.7 parts of electrolytic manganese; 6.8 parts of 80% ferrovanadium; 24.4 parts of 68% high carbon ferrochrome; 8.1 parts of 60% ferroniobium; 22.7 parts of 60% ferromolybdenum; 23.1 parts of 80% tungsten carbide cemented carbide; 2.9 parts of iron powder.
[0040] Preferably, the powder filling rate in the flux core is 30-40%. Generally, the powder filling rate needs to be kept appropriate, otherwise it will affect the performance of the flux-cored welding wire and the stability of the welding process. If the filling rate is too low, the welding wire may not be filled solidly, and powder channeling may easily occur in the subsequent process, and it is easy to be squeezed and flattened by the wire feeding wheel during welding, resulting in uneven wire feeding. At the same time, due to the loose structure of the welding wire, the gas brought into the molten pool increases, which may cause pores in the weld. On the contrary, if the filling rate is too high, it will increase the difficulty of rolling and drawing. In an extreme case, the outer skin cannot wrap the flux core powder, resulting in waste of flux core powder leakage, affecting the rolling process. Therefore, it is necessary to select an appropriate filling rate. In the present invention, after many experiments and demonstrations, when the powder filling rate in the flux core is between 30% and 40%, a better filling effect can be produced, and the flux-cored welding wire obtained by rolling and drawing has a good state. More preferably, the powder filling rate in the flux core is 36%.
[0041] Preferably, the diameter of the flux-cored welding wire is 1.6 mm.
[0042] Preferably, the outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm.
[0043] To achieve the second purpose of the present invention, the following technical solution is adopted:
[0044] A method for preparing an improved high-toughness M2 high-speed steel flux-cored welding wire, the preparation method comprising the following steps:
[0045] S1. Add the components of the core in a drying machine at a temperature of 180-220°C according to the formula, dry them in a drying machine at a temperature of 180-220°C for 2-3 hours, and then put them into a three-dimensional motion mixer to mix them evenly. Then put them into an incubator at a temperature of 140-160°C to keep them warm. The core powder obtained is set aside;
[0046] S2, placing the outer skin on a tape unwinding machine of a flux-cored welding wire forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine;
[0047] S3, adding the flux core powder into the U-shaped groove and controlling the powder filling rate in the flux core to be 30-40%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and drawing it to a diameter of 1.6 mm to obtain a flux cored welding wire.
[0048] Preferably, the temperature in the three-dimensional motion mixer in S1 is 200° C., and the three-dimensional motion mixer can mix the components of the flux-cored welding wire with high uniformity.
[0049] Preferably, the steps of the preparation method further include: S4, winding the flux-cored welding wire layer into a disc to obtain a finished improved high-toughness M2 high-speed steel flux-cored welding wire.
[0050] Beneficial effects of the present invention:
[0051] The improved high-toughness M2 high-speed steel flux-cored welding wire of the present invention has the following properties:
[0052] ① The flux-cored welding wire of the present invention has the characteristics of high wear resistance, wherein the wear resistance can reach 2.5-2.8 times that of Cr26 high chromium cast iron;
[0053] ② In the present invention, the addition of boron, carbon and vanadium elements strengthens the matrix, refines the grains, generates a hard phase, and makes the flux-cored welding wire have high hardness. The Rockwell hardness HRC of the flux-cored welding wire of the present invention is greater than 64;
[0054] ③ The addition of molybdenum and tungsten elements refines the grains, neutralizes and optimizes the affinity between the matrix and the reinforcement, and makes the flux-cored welding wire have high temperature resistance. The flux-cored welding wire of the present invention has a Vickers hardness of HV 850°C. 10 Maintain no less than 580;
[0055] ④ The addition of manganese and chromium elements strengthens and toughens the matrix, neutralizes and optimizes the affinity between the matrix and the reinforcement, reduces the crack tendency, and makes the flux-cored welding wire have the characteristics of less cracks;
[0056] ⑤ The addition of manganese, silicon and nickel elements strengthens and toughens the matrix, thereby improving the toughness of the flux-cored welding wire of the present invention.
[0057] ⑥ Low production cost. While the performance of the flux-cored welding wire of the present invention is close to that of plasma or laser clad powder, the production cost of the flux-cored welding wire of the present invention is significantly lower than that of plasma or laser clad powder. The production cost of the flux-cored welding wire of the present invention is only 40-50 yuan / kg, while the production cost of plasma or laser clad powder reaches 170-180 yuan / kg.
[0058] ⑦ The preparation method of the flux-cored welding wire of the present invention is simple and easy to use, and can be directly welded manually or automatically by a machine, which is conducive to industrial production;
[0059] ⑧ The single-layer surfacing of the flux-cored welding wire of the present invention has uniform structure, no sharp-angle hard phase, and no cracking in multiple layers of surfacing. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a microstructure diagram of flux-cored wire surfacing according to Example 2 of the present invention. DETAILED DESCRIPTION
[0061] The present invention can be further understood by the specific examples of the present invention given below, but they are not intended to limit the present invention.
[0062] Example 1
[0063] The present embodiment 1 provides an improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, comprises the following components: boron B: 0.5%; carbon C: 0.6%; silicon Si: 1.0%; manganese Mn: 0.3%; vanadium V: 1.0%; nickel Ni: 0.3%; cobalt Co: 0.3%; chromium Cr: 3.0%; niobium Nb: 1.5%; molybdenum Mo: 5.0%; tungsten W: 6.0%, and iron Fe: 80.5%.
[0064] In this embodiment 1, boron B is obtained from boron carbide and borax; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon; manganese Mn is obtained from electrolytic manganese; vanadium V is obtained from 80% ferrovanadium; nickel Ni is obtained from nickel powder; cobalt Co is obtained from cobalt powder; chromium Cr is obtained from 68% high carbon ferrochrome; niobium Nb is obtained from 60% ferroniobium; molybdenum Mo is obtained from 60% ferromolybdenum; tungsten W, nickel Ni and cobalt Co are obtained from tungsten powder; and iron Fe is obtained from iron powder.
[0065] The preparation steps of the improved high-toughness M2 high-speed steel flux-cored welding wire of this embodiment 1 are as follows:
[0066] S1, add 1.9 parts of boron carbide, 1.5 parts of borax, 0.4 parts of graphite, 3.8 parts of 75% ferrosilicon, 0.4 parts of electrolytic manganese, 4.3 parts of 80% ferrovanadium, 12.2 parts of 68% high carbon ferrochrome, 6.4 parts of 60% ferroniobium, 22.7 parts of 60% ferromolybdenum, 23.1 parts of 80% tungsten carbide and 2.7 parts of iron powder in a drying machine at a temperature of 180°C and bake for 2h, then put into a three-dimensional motion mixer at a temperature of 200°C and mix well, then put into an incubator at a temperature of 140°C to keep warm, and the obtained core powder is ready for use;
[0067] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a strip unwinding machine of a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0068] S3, adding flux core powder to the U-shaped groove and controlling the powder filling rate in the flux core to 30%, the forming machine rolls and closes the U-shaped groove after adding the flux core powder and pulls it to a diameter of 1.6 mm to obtain a flux cored welding wire.
[0069] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of improved high-toughness M2 high-speed steel flux-cored welding wire.
[0070] Example 2
[0071] The present embodiment 2 provides an improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, comprises the following components: boron B: 1.0%; carbon C: 0.9%; silicon Si: 1.3%; manganese Mn: 0.6%; vanadium V: 1.6%; nickel Ni: 0.5%; cobalt Co: 0.5%; chromium Cr: 6.0%; niobium Nb: 1.9%; molybdenum Mo: 5.0%; tungsten W: 6.0%; iron: 74.7%.
[0072] In this embodiment 2, boron B is obtained from boron carbide and borax; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon; manganese Mn is obtained from electrolytic manganese; vanadium V is obtained from 80% ferrovanadium; nickel Ni is obtained from nickel powder; cobalt Co is obtained from cobalt powder; chromium Cr is obtained from 68% high carbon ferrochrome; niobium Nb is obtained from 60% ferroniobium; molybdenum Mo is obtained from 60% ferromolybdenum; tungsten W, nickel Ni and cobalt Co are obtained from tungsten powder; and iron Fe is obtained from iron powder.
[0073] The preparation steps of the improved high-toughness M2 high-speed steel flux-cored welding wire of Example 2 are as follows:
[0074] S1, add 3.8 parts of boron carbide, 1.7 parts of borax, 0.7 parts of graphite, 5.0 parts of 75% ferrosilicon, 0.7 parts of electrolytic manganese, 6.8 parts of 80% ferrovanadium, 24.4 parts of 68% high carbon ferrochrome, 8.1 parts of 60% ferroniobium, 22.7 parts of 60% ferromolybdenum, 23.1 parts of 80% tungsten carbide and 2.9 parts of iron powder in a drying machine at a temperature of 200°C for 2.5h, then put them into a three-dimensional motion mixer at a temperature of 200°C to mix them evenly, then put them into an incubator at a temperature of 150°C to keep them warm, and the obtained core powder is used for standby;
[0075] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a strip unwinding machine of a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0076] S3, adding flux core powder to the U-shaped groove and controlling the powder filling rate in the flux core to be 36%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and drawing it to a diameter of 1.6 mm to obtain a flux cored welding wire;
[0077] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of improved high-toughness M2 high-speed steel flux-cored welding wire.
[0078] like Figure 1 As shown in the microstructure diagram, the single-layer surfacing structure is uniform and there is no sharp-angle hard phase.
[0079] The flux-cored welding wire of Example 2 does not crack when multiple layers are built-up to a thickness of 40 mm.
[0080] Example 3
[0081] The present embodiment 3 provides an improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, the chemical composition of the deposited metal of the flux-cored welding wire, by weight percentage, comprises the following components: boron B: 1.6%; carbon C: 1.3%; silicon Si: 1.6%; manganese Mn: 0.9%; vanadium V: 2.2%; nickel Ni: 0.7%; cobalt Co: 0.7%; chromium Cr: 8.0%; niobium Nb: 2.2%; molybdenum Mo: 5.0%; tungsten W: 6.0%, iron Fe: 69.8%.
[0082] In this embodiment 3, boron B is obtained from boron carbide and borax; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon; manganese Mn is obtained from electrolytic manganese; vanadium V is obtained from 80% ferrovanadium; nickel Ni is obtained from nickel powder; cobalt Co is obtained from cobalt powder; chromium Cr is obtained from 68% high carbon ferrochrome; niobium Nb is obtained from 60% ferroniobium; molybdenum Mo is obtained from 60% ferromolybdenum; tungsten W, nickel Ni and cobalt Co are obtained from tungsten powder; iron Fe is obtained from iron powder.
[0083] The preparation steps of the improved high-toughness M2 high-speed steel flux-cored welding wire of this embodiment 3 are as follows:
[0084] S1, add 6.1 parts of boron carbide, 1.8 parts of borax, 0.9 parts of graphite, 6.2 parts of 75% ferrosilicon, 1.1 parts of electrolytic manganese, 9.4 parts of 80% ferrovanadium, 32.5 parts of 68% high carbon ferrochrome, 9.4 parts of 60% ferroniobium, 22.7 parts of 60% ferromolybdenum, 23.1 parts of 80% tungsten carbide and 3.1 parts of iron powder in a drying machine at a temperature of 180°C and bake for 3 hours, then put them into a three-dimensional motion mixer at a temperature of 200°C and mix them evenly, then put them into an incubator at a temperature of 160°C to keep them warm, and the obtained core powder is used for standby;
[0085] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a strip unwinding machine of a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0086] S3, adding flux core powder to the U-shaped groove and controlling the powder filling rate in the flux core to be 40%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and drawing it to a diameter of 1.6 mm to obtain a flux cored welding wire;
[0087] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of improved high-toughness M2 high-speed steel flux-cored welding wire.
[0088] Example 4
[0089] The present embodiment 4 provides an improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, and the chemical composition of the deposited metal of the flux-cored welding wire, measured by weight percentage, comprises the following components: boron B: 1.2%; carbon C: 0.8%; silicon Si: 1.2%; manganese Mn: 0.7%; vanadium V: 1.8%; nickel Ni: 0.4%; cobalt Co: 0.4%; chromium Cr: 7.0%; niobium Nb: 2.0%; molybdenum Mo: 5.0%; tungsten W: 6.0%; aluminum Al: 0.5%; iron Fe: 73.0%.
[0090] In this embodiment 4, boron B is obtained from boron carbide and borax; carbon C is obtained from graphite; silicon Si is obtained from 75% ferrosilicon; manganese Mn is obtained from electrolytic manganese; vanadium V is obtained from 80% ferrovanadium; nickel Ni is obtained from nickel powder; cobalt Co is obtained from cobalt powder; chromium Cr is obtained from 68% high carbon ferrochrome; niobium Nb is obtained from 60% ferroniobium; molybdenum Mo is obtained from 60% ferromolybdenum; tungsten W, nickel Ni and cobalt Co are obtained from tungsten powder; aluminum Al is obtained from aluminum powder; iron Fe is obtained from iron powder.
[0091] The preparation steps of the improved high-toughness M2 high-speed steel flux-cored welding wire of this embodiment 4 are as follows:
[0092] S1. Add 4.2 parts of boron carbide, 1.7 parts of borax, 0.6 parts of graphite, 4.1 parts of 75% ferrosilicon, 0.8 parts of electrolytic manganese, 6.5 parts of 80% ferrovanadium, 25.6 parts of 68% high carbon ferrochrome, 8.0 parts of 60% ferroniobium, 22.7 parts of 60% ferromolybdenum, 23.1 parts of 80% tungsten carbide, 1.9 parts of aluminum powder, and 2.8 parts of iron powder in a drying machine at a temperature of 200°C and bake for 2.5 hours, then put them into a three-dimensional motion mixer at a temperature of 200°C and mix them evenly, then put them into an incubator at a temperature of 150°C to keep them warm, and the obtained core powder is ready for use;
[0093] S2, placing a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm on a strip unwinding machine of a flux-cored welding wire forming machine, and rolling the low-carbon steel strip into a U-shaped groove by the forming machine;
[0094] S3, adding flux core powder to the U-shaped groove and controlling the powder filling rate in the flux core to be 36%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and drawing it to a diameter of 1.6 mm to obtain a flux cored welding wire;
[0095] S4. Wind the flux-cored welding wire layer into a coil to obtain a finished product of improved high-toughness M2 high-speed steel flux-cored welding wire.
[0096] Example 5
[0097] This embodiment 5 provides an improved high-toughness M2 high-speed steel flux-cored welding wire, which is different from the embodiment 4 in that the weight percentage of aluminum Al is 0.2%, the aluminum powder is 0.8 parts, the weight percentage of iron Fe is 73.3%, and the remaining components and the preparation method of the flux-cored welding wire are the same as those in the embodiment 4 and will not be repeated here.
[0098] Example 6
[0099] Wear resistance test
[0100] According to the loose abrasive wear test method of JB / T 7705-1995, the wear resistance of the flux-cored welding wires prepared in Examples 1-5 and commercially available Cr26 high chromium cast iron, M2 powder metallurgy high-speed steel, and M2 high-speed steel deposited powder were tested. The test results are shown in Table 1.
[0101] Table 1 Wear resistance test results
[0102]
[0103]
[0104] Example 7
[0105] Hardness performance test
[0106] According to the test methods in GB / T 230.1-2009 Rockwell hardness test for metal materials and GB / T 4340.1-2009 Vickers hardness test for metal materials, the flux-cored welding wires prepared in Examples 1-5 and commercially available Cr26 high chromium cast iron, M2 powder metallurgy high-speed steel, and M2 high-speed steel deposited powder were subjected to Rockwell hardness performance tests and Vickers hardness performance tests, respectively. The test results are shown in Table 2 and Table 3, respectively.
[0107] Table 2 Rockwell hardness performance test results
[0108]
[0109] Table 3 Vickers hardness performance test results
[0110]
[0111] Analyze the results of Tables 1-3 above:
[0112] From the results in Table 1, it can be seen that the wear weight loss of the flux-cored welding wires prepared in Examples 1-5 is significantly lower than the wear weight loss of Cr26 high chromium cast iron, better than the wear weight loss of M2 high-speed steel deposited powder, and relatively close to the wear weight loss of M2 powder metallurgy high-speed steel. Among them, the wear weight loss of Cr26 high chromium cast iron reaches 2.8 times the wear weight loss of the flux-cored welding wire prepared in Example 2 (multiple = wear weight loss of Cr26 high chromium cast iron ÷ wear weight loss of flux-cored welding wire in Example 2).
[0113] From the results in Table 2, it can be seen that the Rockwell hardness of the flux-cored welding wires prepared in Examples 1-5 is stronger than the Rockwell hardness of Cr26 high chromium cast iron, and relatively lower than the Rockwell hardness of M2 powder metallurgy high-speed steel and the Rockwell hardness of M2 high-speed steel deposited powder.
[0114] From the results in Table 3, it can be seen that the Vickers hardness of the flux-cored welding wire prepared in Examples 1-5 can still be maintained at more than 580 at a temperature of 850°C, which is significantly stronger than the Vickers hardness of Cr26 high chromium cast iron under the same conditions, and relatively lower than the Vickers hardness of M2 powder metallurgy high-speed steel and the Vickers hardness of M2 high-speed steel deposited powder.
[0115] From the results in Tables 2-3 above and based on the relationship in material mechanics, it can be judged that, in general, the hardness and toughness of a material are negatively correlated. Therefore, it can be judged that the toughness of the flux-cored welding wire prepared in Examples 1-5 is stronger than the toughness of M2 powder metallurgy high-speed steel and the toughness of M2 high-speed steel deposited powder.
[0116] From the results in Tables 1-3 above, it can be seen that the hardness test results of Examples 4 and 5, which are flux-cored welding wires made by adding aluminum powder, are compared with the hardness test results of Example 1-3 without adding aluminum powder. It can be seen that the hardness of Example 4-5 is lower than that of Example 1-3. According to the material property relationship under normal conditions: the higher the hardness, the greater the brittleness and the lower the toughness. It can be seen that the toughness of Example 4-5 is stronger than that of Example 1-3, indicating that the addition of aluminum powder is beneficial to enhancing the toughness of the flux-cored welding wire.
[0117] In summary, the wear resistance of the flux-cored welding wire obtained in Examples 1-5 is stronger than that of Cr26 high chromium cast iron and M2 high-speed steel deposited powder, and is close to that of M2 powder metallurgy high-speed steel. The toughness of the flux-cored welding wire obtained in Examples 1-5 is stronger than that of M2 high-speed steel deposited powder and M2 powder metallurgy high-speed steel. However, from the cost point of view, the cost price of the flux-cored welding wire obtained in Examples 1-5 of the present invention is 40 to 50 yuan / kg, while the production cost price of M2 powder metallurgy high-speed steel and M2 high-speed steel deposited powder is 170 to 180 yuan / kg. It can be seen that the cost of the flux-cored welding wire obtained in Examples 1-5 is about 30% of the cost of M2 powder metallurgy high-speed steel. Obviously, the flux-cored welding wire of the present invention has a price advantage, can save production costs, and conforms to the economic elements of modern industrial production.
[0118] The above is only an implementation method of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An improved high-toughness M2 high-speed steel flux-cored welding wire, the flux-cored welding wire comprising an outer skin and a flux core filled in the outer skin, characterized in that: The chemical composition of the deposited metal of the flux-cored welding wire includes the following components by weight percentage: Boron: 0.5-1.6%; Carbon: 0.6-1.3%; Silicon: 1-1.6%; Manganese: 0.3-0.9%; Vanadium: 1-2.2%; Nickel: 0.3-0.7%; Cobalt: 0.3-0.7%; Chromium: 3-8%; Niobium: 1.5-2.2%; Molybdenum: 5%; Tungsten: 6%; the balance is iron.
2. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1 is characterized in that: The chemical composition of the deposited metal of the flux-cored welding wire includes the following components by weight percentage: Boron: 1.0%; Carbon: 1.0%; Silicon: 1.3%; Manganese: 0.6%; Vanadium: 1.6%; Nickel: 0.5%; Cobalt: 0.5%; Chromium: 6%; Niobium: 1.9%; Molybdenum: 5%; Tungsten: 6%; Iron 74.7%.
3. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1, characterized in that: The chemical composition of the deposited metal of the flux-cored welding wire also includes aluminum, the weight percentage of the aluminum is 0.2-0.5%, and the aluminum exists in the form of aluminum powder.
4. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1 or 2, characterized in that: The boron exists in the form of boron carbide and borax; the carbon exists in the form of graphite; the silicon exists in the form of 75% ferrosilicon; the manganese exists in the form of electrolytic manganese; the vanadium exists in the form of 80% ferrovanadium; the chromium exists in the form of 68% high-carbon ferrochrome; the niobium exists in the form of 60% ferroniobium; the molybdenum exists in the form of 60% ferromolybdenum; the tungsten, the nickel and the cobalt exist in the form of 80% tungsten carbide cemented carbide; and the iron exists in the form of iron powder.
5. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1 or 2, characterized in that: The filling rate of the medicine powder in the medicine core is 30-40%.
6. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1 or 2, characterized in that: The diameter of the flux-cored welding wire is 1.6 mm.
7. The improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 1 or 2, characterized in that: The outer skin is a low-carbon steel strip with a thickness of 0.4 mm and a width of 14 mm.
8. A method for preparing the improved high-toughness M2 high-speed steel flux-cored welding wire according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1. Add the components of the core in a drying machine at a temperature of 180-220°C according to the formula, dry them in a drying machine at a temperature of 180-220°C for 2-3 hours, and then put them into a three-dimensional motion mixer to mix them evenly. Then put them into an incubator at a temperature of 140-160°C to keep them warm. The core powder obtained is set aside; S2, placing the outer skin on a tape unwinding machine of a flux-cored welding wire forming machine, and rolling the outer skin steel strip into a U-shaped groove by the forming machine; S3, adding the flux core powder into the U-shaped groove and controlling the powder filling rate in the flux core to be 30-40%, the forming machine rolling and closing the U-shaped groove after adding the flux core powder and drawing it to a diameter of 1.6 mm to obtain a flux cored welding wire.
9. The method for preparing the improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 8, characterized in that: The temperature in the three-dimensional motion mixer in S1 is 200°C.
10. The method for preparing the improved high-toughness M2 high-speed steel flux-cored welding wire according to claim 8, characterized in that: The steps of the preparation method also include: S4, winding the flux-cored welding wire layer into a coil to obtain a finished improved high-toughness M2 high-speed steel flux-cored welding wire.
Citation Information
Patent Citations
Filling soldering flux wire for titania gas coverage arc welding
CN101157169A
Hard-facing alloys having improved crack resistance
CN101421073A
Metal type flux-cored wire for WH80 and 20Mn23Al and preparation method of metal type flux-cored wire
CN108555479A
Gas-shielded arc welding wire and gas-shielded arc welding method
CN111448029A
Flux-cored wire for gas shielded arc welding for reducing welding deformation, and method of reducing welding deformation with flux-cored wire
JP2005144539A
Cited By
High-hardness and high-toughness laser cladding flux-cored wire and application thereof
CN121267461A